Seismic Retrofit of Substandard RC Columns Using Sprayed Glass Fiber-Reinforced Mortar and Basalt Textile Reinforcement - Ateş, Ali Osman; Hajihosseinlou, Saeid; Nasrinpour, Amin; Demir, Cem; CÖMERT, MUSTAFA; Maraşlı, Muhammed; İlki, Alper (Taylor & Francis Ltd., 2023)
This study investigates the seismic retrofit of substandard reinforced concrete (RC) columns through external jacketing of potential plastic hinge zones using sprayed glass fiber-reinforced mortar and basalt textile reinforcement. An innovative spraying method was used to apply the matrix material to the concrete surface. A total number of eight full-scale columns (four reference, four retrofitted) were tested under constant high axial load to capacity ratio and reversed cyclic lateral loading. Columns were constructed using low-strength concrete and transverse reinforcement with various spacing and inadequate hook detailing to mimic the columns in substandard structures. Test results are evaluated in terms of lateral load-drift ratio relationships, displacement ductility, stiffness degradation, energy dissipation, and residual displacements. Evaluation of the test results showed that the proposed technique is effective for seismic retrofit of substandard RC columns, particularly in terms of enhancement of displacement ductility, energy dissipation capacities, and reduction of residual displacements.
Keywords: Seismic Retrofit; Substandard Columns; Cement-Based Composites; External Jacketing; TRM